2017
DOI: 10.1002/jso.24942
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic staging laparoscopy in gastric cancer treatment: A cost‐effectiveness analysis

Abstract: The cost-effectiveness of DSL for GC patients is highly dependent on patient and test characteristics, and is more likely when DSL is used selectively where procedure yield is high, such as for locally advanced disease or in detecting peritoneal and superficial versus deep liver lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…This result supports the use of the procedure when patients have potential risk factors for hidden disease on imaging exams 12 .…”
Section: Introductionsupporting
confidence: 70%
“…This result supports the use of the procedure when patients have potential risk factors for hidden disease on imaging exams 12 .…”
Section: Introductionsupporting
confidence: 70%
“…Almost all advanced gastric cancer patients may be candidates for SL, but it is not a realistic goal. Li et al from the USA reported the problem of cost‐effectiveness . Accordingly, advanced gastric cancer patients with a high possibility of peritoneal dissemination among clinically P0 patients should undergo SL.…”
Section: Discussionmentioning
confidence: 99%
“…A proportion of patients was found to have unsuspected, unresectable factors for tumor during LE. The cost-effective analysis also supported the validation of LE in gastric cancer patients [ 17 ]. However, there was still no consolidated inclusion criteria for LE in gastric cancer patients since the distribution of stage was very distinguished from each other [ 18 , 19 ].…”
mentioning
confidence: 78%